ПЕРСПЕКТИВЫ ИНФОРМАЦИОННОГО РАЗВИТИЯ МАРКЕТИНГОВОЙ ДЕЯТЕЛЬНОСТИ НА ОТРАСЛЕВОМ УРОВНЕ - S. Ashmarina; O. Pudovkina (Вестник университета, 2018)
The basic tendencies of information and marketing development of the heavy engineering industry are analyzed and the peculiarities of their growth are revealed. The basic principles of the creation of a unified information management system in the field of marketing which is based on the conceptual provisions of the strategy for the development of the heavy engineering industry have been formulated. The creation of a center for management of branch marketing information flows based on vertical and horizontal interaction between the industry levels and contributing to the increase in the effectiveness of information support for the enterprises of the machine-building complex at the industry level has been proposed.